2015
DOI: 10.1042/bj20141133
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofLeishmania donovaniperoxin 14 residues required for binding the peroxin 5 receptor proteins

Abstract: Trafficking of peroxisomal targeting signal 1 (PTS1) proteins to the Leishmania glycosome is dependent on the docking of the LdPEX5 receptor to LdPEX14 on the glycosomal membrane. A combination of deletion and random mutagenesis was used to identify residues in the LdPEX14 N-terminal region that are critical for mediating the LdPEX5-LdPEX14 interaction. These studies highlighted residues 35-75 on ldpex14 as the core domain required for binding LdPEX5. Single point mutation within this core domain generally did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 40 publications
1
11
1
Order By: Relevance
“…Biochemical studies with the N-terminal domain of LdPEX14 confirmed that an analogous region encompassing residues 35-75 was also sufficient for binding LdPEX5 [25]. Interestingly, the Leishmania PEX14 fragment lacked a threonine residue at position 31 (T31) which in the human PEX14 was shown to be critical for stabilizing PEX5 binding, but instead contained a serine residue (S36) at the corresponding position.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Biochemical studies with the N-terminal domain of LdPEX14 confirmed that an analogous region encompassing residues 35-75 was also sufficient for binding LdPEX5 [25]. Interestingly, the Leishmania PEX14 fragment lacked a threonine residue at position 31 (T31) which in the human PEX14 was shown to be critical for stabilizing PEX5 binding, but instead contained a serine residue (S36) at the corresponding position.…”
Section: Introductionmentioning
confidence: 84%
“…pET30b-ldpex14 (21-75) construct was generated by cloning the PCR fragment encompassing the LdPEX14 residues 21-75 into NdeI and XhoI restriction sites of pET30b vector. Generation of pUT18C-LdPEX14 and pKT25-LdPEX5 for bacterial two-hybrid experiments and pET30b-ldpex14 (1-120), pTYB12-LdPEX5, and pTYB12-ldpex5 (203-390) for protein expression were previously described [25]. The integrity of all vectors was validated by automated DNA sequencing.…”
Section: Cloning and Mutagenesismentioning
confidence: 99%
See 3 more Smart Citations